Initiation Practices and Access to Higher Education for Deaf Students: The Interpreter as a Resource - Barbosa, Susana (2023)
The transition from secondary school to higher education institutions (HEIs) can be a very exciting experience, but it can also represent unique challenges, making this moment a crucial event in the academic path of all students. Academic initiation practices are a tradition that exists on several universities campuses with the purpose of promoting students' integration into academic life during such an important transition. It is important to analyse the participation of deaf students in initiation practices to higher education and the sign language interpreters' role in including them in this process. Sixteen deaf students of HEIs in the Porto region participated in this study and accepted the importance of initiation, although some interviewees were afraid they would not have enough time to dedicate to their studies, which influenced their decision not to take part in these activities. Deaf students who participated and experienced initiation rituals identified several constraints, which indicates that academic initiation practices are not adapted to the specific needs of deaf students, nor to the needs of the deaf community as a whole. HEIs are not fully aware of the need to adapt them, so that all students, regardless of their hearing ability, can fully participate and feel included at university. It is vital to provide conditions that allow the full inclusion of deaf students into the academic environment. Since Portuguese sign language is the language of these students, it is essential for them to have an interpreter who facilitates communication in both educational situations and extracurricular activities they wish to participate in, thus minimizing discrimination and promoting full inclusion.